Kefiran-alginate gel microspheres for oral delivery of ciprofloxacin - Blandón, Lina M. (2016)
Ciprofloxacin is a broad-spectrum antibiotic associated with gastric and intestinal side effects after extended oral administration. Alginate is a biopolymer commonly employed in gel synthesis by ionotropic gelation, but unstable in the presence of biological metal-chelating compounds and/or under dried conditions. Kefiran is a microbial biopolymer able to form gels with the advantage of displaying antimicrobial activity. In the present study, kefiran-alginate gel microspheres were developed to encapsulate ciprofloxacin for antimicrobial controlled release and enhanced bactericidal effect against common pathogens. Scanning electron microscopy (SEM) analysis of the hybrid gel microspheres showed a spherical structure with a smoother surface compared to alginate gel matrices. In vitro release of ciprofloxacin from kefiran-alginate microspheres was less than 3.0% and 5.0% at pH 1.2 (stomach), and 5.0% and 25.0% at pH 7.4 (intestine) in 3 and 21 h, respectively. Fourier transform infrared spectroscopy (FTIR) of ciprofloxacin-kefiran showed the displacement of typical bands of ciprofloxacin and kefiran, suggesting a cooperative interaction by hydrogen bridges between both molecules. Additionally, the thermal analysis of ciprofloxacin-kefiran showed a protective effect of the biopolymer against ciprofloxacin degradation at high temperatures. Finally, antimicrobial assays of Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Salmonella typhymurium, and Staphylococcus aureus demonstrated the synergic effect between ciprofloxacin and kefiran against the tested microorganisms.